Correlation study of optical, mechanical and thermal properties of BAs material and its experimental energy gap - Daoud, Salah (International Journal of Physical Research, 2017)
The object of this work is to study the correction between the optical, mechanical and thermal properties of boron arsenide (BAs) material and its experimental optical energy gap. The index of refraction, the high-frequency dielectric constant, the optical electronegativity, the bulk modulus, the micro-hardness, the plasmon energy, the Debye temperature, the melting temperature and the electronic polarizability of BAs were estimated from its energy gap. The results obtained are analyzed in comparison with available experimental and other theoretical data. My obtained results of the reflective index and the dielectric constant agree well with other theoretical data; whereas the bulk modulus, the microhardness, the Debye temperature, and the melting temperature are slightly lower than the experimental and other theoretical data. The electronic polarizability is slightly different than other theoretical ones from the literature.